Bifunctional Manipulation of Terahertz Waves with High‐Efficiency Transmissive Dielectric Metasurfaces. Issue 4 (9th December 2022) - Wang, Zhuo; Yao, Yao; Pan, Weikang; Zhou, Haoyang; Chen, Yizhen; Lin, Jing; Hao, Jiaming; Xiao, Shiyi; He, Qiong; Sun, Shulin; Zhou, Lei
Abstract: Multifunctional terahertz (THz) devices in transmission mode are highly desired in integration‐optics applications, but conventional devices are bulky in size and inefficient. While ultra‐thin multifunctional THz devices are recently demonstrated based on reflective metasurfaces, their transmissive counterparts suffer from severe limitations in efficiency and functionality. Here, based on high aspect‐ratio silicon micropillars exhibiting wide transmission‐phase tuning ranges with high transmission‐amplitudes, a set of dielectric metasurfaces is designed and fabricated to achieve efficient spin‐multiplexed wavefront controls on THz waves. As a benchmark test, the photonic‐spin‐Hall‐effect is experimentally demonstrated with a record high absolute efficiency of 92% using a dielectric metasurface encoded with geometric phases only. Next, spin‐multiplexed controls on circularly polarized THz beams (e.g., anomalous refraction and focusing) are experimentally demonstrated with experimental efficiency reaching 88%, based on a dielectric meta‐device encoded with both spin‐independent resonant phases and spin‐dependent geometric phases. Finally, high‐efficiency spin‐multiplexed dual holographic images are experimentally realized with the third meta‐device encoded with both resonant and geometric phases. Both near‐field and far‐field measurements are performed to characterize these devices, yielding results in agreement with full‐wave simulations. The study paves the way to realize multifunctional, high‐performance, and ultra‐compact THz devices for applications in biology sensing, communications, and so on. Abstract : High‐quality dielectric metasurfaces are experimentally demonstrated to achieve efficient spin‐multiplexed wavefront controls on transmissive terahertz lights, including photonic spin Hall effect, anomalous refraction and focusing, and holographic dual‐images. The adopted high aspect‐ratio silicon meta‐atoms exhibit high transmission, large phase accumulation, and desired cross‐polarization conversion ability, simultaneously. This work can stimulate realization of many high‐efficiency, ultra‐compact, and multifunctional terahertz devices.